The linguistic Standard and its levels and its impact in the statement of Quranic miracles الضابط اللغوي ومستوياته وأثره في بيان الإعجاز القرآني - Muhammad Abbas Nehaia Al-Gerayawi محمد عباس نهاية الجرياوي (Journal Of Babylon Center For Humanities Studies, 2019)
As each work has an end, and each scientific effort concludes, the research ultimately wishes to recall its most important findings: 1- Detect of the research that one of the miracles of the Holy Quran carried the verbal joint on all meanings unless there is a presumption that prevents one of its meanings, as it addresses all ages and various aspects of miracle. 2- One of the most important standards in the statement of the miracle of the Holy Quran is the grammatical standard, it reveals the miracles of the book of God Almighty. 3- That one of the most important distinguishing features of the Holy Quran in its miracles is its words that suit its semantic development. The word in the Holy Quran is placed in a place suitable for all times and places. 4- After taking an example of each type of Eloquence, we find that Eloquence Standards and their study are important in discovering the miracle of the Holy Quran and understanding its precious signs. الحمد لله رب العالمين، الذي أنزل كتابه المبين هدى وبشرى للمؤمنين، وتحدى به الخلق أن يأتوا بمثله مجتمعين، والصلاة والسلام على أشرف الأنبياء والمرسلين محمد وعلى آله الطاهرين. وبعد ... لعل من دواعي كثرة الدراسات القرآنية أن هذا الكتاب قد بهر الناس قديماً وحديثاً، وجعلهم عاجزين عن مجاراته، بل الإتيان بآية من آياته، مما دفع العلماء إلى البحث عن أسباب إعجازه. ولأهمية الإعجاز القرآني ، ترسم الباحث دراسة موضوع الضابط اللغوي ومستوياته وأثره في بيان إعجاز القرآن رغبةً منه في دراسة كتاب الله الكريم والكشف عما يحمله من أوجه إعجازية . ولا شك في أن للغة حضورها الكبير في فهم النص القرآني ، إذ لا يمكن فهم النص ، إلاّ من خلال الإلمام بحلته اللغوية ، ودرسنا في هذا البحث عدد من الضوابط اللغوية مقسمةً على خمسة مطالب يسبقها تمهيد يبين المدلول اللغوي والاصطلاحي للضابط ، وهذه الضوابط هي اللغوية والنحوية والدلالية والبلاغية والاسلوبية. وأخيراً يرجو الباحث من الله تعالى أن يجعل هذا العمل خالصاً لوجهه الكريم .